Gender Alert: Gender and Displacement in Lebanon at the Juncture of the Ceasefire - United Nations Women (United Nations, 2025)
Between October 2023 and late November 2024, Lebanon experienced the largest escalation of hostilities with Israel since the 2006 War. Intense Israeli airstrikes coupled with evacuation orders across Lebanon, including in eastern and southern Lebanon and the southern suburbs of Beirut, resulted in mass displacement and heightened socioeconomic vulnerabilities among affected populations. As of 24 November 2024, close to 900,000 individuals were displaced due to the conflict, with women and girls making up 51 per cent of the internally displaced population. Of an estimated 260,000 households, close to 21 per cent were women-led households. Additionally, more than 80,000 Syrians and 3,466 Palestinian refugees in Lebanon were among the displaced. The conflict took a profound toll on people’s lives. Lebanese health officials estimate that, since the escalation of hostilities on 8 October 2023, 4,047 people have been killed and 16,638 wounded, including at least 790 women and 316 children. As commonly witnessed in other contexts, this latest Gender Alert confirms that while the conflict impacts civilians indiscriminately, women and girls have been disproportionately affected due to multiple and intersecting forms of discrimination that heighten their exclusion and risks.